Environmentally Relevant Level of Aflatoxin B1 Dysregulates Human Dendritic Cells Through Signaling on Key Toll-Like Receptors. (May 2014) - Mohammadi, Azam; Mehrzad, Jalil; Mahmoudi, Mahmoud; Schneider, Marion
Aflatoxins (AFs) are highly hazardous fungal biometabolites usually present in feeds and foods. Aflatoxin B1 (AFB1 ) is the most toxic and a known carcinogen. Toll-like receptors (TLRs), highly expressed by myeloid dendritic cells (DC), are key innate immune-surveillance molecules. Toll-like receptors not only sense pathogen-associated molecular patterns but also contribute to infections and cancer. To assess AFB1 –TLR interactions on human myeloid DC, pure CD11c + DC were generated from monocytes isolated from healthy individuals and then exposed to relevant level of AFB1 for 2 hours. Both quantitative polymerase chain reaction and flow cytometric assays were used to quantify, respectively, expression of TLR2 and TLR4 at the messenger RNA (mRNA) and protein levels in these DC. Levels of interleukin (IL) 1β, IL-6, and IL-10 were also analyzed in AFB1 - and mock-treated DC. Compared to nontreated CD11c + DC, expression levels of both TLR2 and TLR4 mRNA and proteins were significantly upregulated in AFB1 -treated cells. Further, although IL-10 levels in AFB1 -treated DC were similar to those in the mock-treated DC, the AFB1 -exposed DC secreted higher amounts of IL-1β and IL-6. Dendritic cells are sensitive to environmentally relevant level of AFB1, and TLR2 and TLR4 are involved in sensing AFB1 . Considering the broad roles of TLR2, TLR4, and DC in immunity and infections, our novel findings open a new door to understanding the molecular mechanisms and functional consequences of AFB1 in inducing immunodysregulation, immunotoxicity, and thus (non)infectious diseases in humans.